SOCIO-CULTURAL MEASURES OF EDUCATION DEVELOPMENT IN THE TERRITORY OF GALICIA AND NADDNIPRYANSHCHYNA (XVIII - XIX CENTURIES) - Chymak, Mykola (Mountain School of Ukrainian Carpaty, 2018)
The article deals with the fundamental activity of progressive representatives of Ukrainian educators of a certain epoch on the way to achieving socio-cultural optimum. The rethinking of the acute need for Ukraine to enter the European educational space has actualized the author's task - a deep retrospective reconsideration of the historical and pedagogical events of previous centuries, with a view to interpret more thoroughly the experience of the Enlighteners of the past generations and define their general significance for the further development of our state. The purpose of the article is to reveal the socio-cultural dimensions of the development of education in the territory of Galicia and Naddnipryanshchyna in the context of the XVIII - XIX centuries. The author investigates the multidimensionality of the main directions and forms of work of education and science representatives during the studied historical period. The research tools for the study were chronological and content, incremental, historical, pedagogical and comparative methods. The use of a whole range of methodological research tools allowed to determine that the activities of the progressive scientific and educational elite of the time, which continued to widely disseminate high-education ideas on the pro-Ukrainian territory, became the basis for more advanced development of vocational education.